Frontispiece: Antimicrobial Peptide Structures: From Model Membranes to Live Cells. Issue 2 (9th January 2018) - Sani, Marc‐Antoine; Separovic, Frances
Abstract : The antimicrobial peptide, maculatin 1.1, forms a transmembrane pore in a phospholipid membrane. The peptide is unstructured in aqueous solution but forms an amphipathic α‐helix in a lipid environment, which is able to insert into the membrane bilayer and lyse bacterial cells. For more information, see the Concept article by M.‐A. Sani and F. Separovic onpage 286 ff.